2016
DOI: 10.1200/jco.2015.64.6448
|View full text |Cite
|
Sign up to set email alerts
|

Proposed Staging System for Patients With HPV-Related Oropharyngeal Cancer Based on Nasopharyngeal Cancer N Categories

Abstract: Purpose Patients with human papillomavirus (HPV)–related oropharyngeal cancer (OPC) generally present with more advanced disease but have better survival than patients with HPV-unrelated OPC. The current American Joint Commission on Cancer (AJCC)/Union for International Cancer Control (UICC) TNM staging system for OPC was developed for HPV-unrelated OPC. A new staging system is needed to adequately predict outcomes of patients with HPV-related OPC. Patients and Methods Patients with newly diagnosed HPV-positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
64
2
1

Year Published

2016
2016
2019
2019

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 68 publications
(70 citation statements)
references
References 27 publications
3
64
2
1
Order By: Relevance
“…Although imputation of HPV status in the CUP cohort introduces uncertainty that this study may have included HPV‐negative patients, this risk is low as demonstrated by the validated model above and supported by the anatomic distribution of nodal disease in the imputed cohort. Furthermore, the imputation of HPV status has been used in the past to improve statistical power . In the unlikely (<1 in 5) event of a false‐positive inclusion (i.e., inclusion of a patient who was truly HPV negative), this erroneously included patient's risk of recurrence or death would likely be higher than a true HPV‐positive patient, further reinforcing our conclusions that HPV‐induced CUP patients have an excellent prognosis, similar to HPV‐induced OPX cancer.…”
Section: Discussionsupporting
confidence: 59%
“…Although imputation of HPV status in the CUP cohort introduces uncertainty that this study may have included HPV‐negative patients, this risk is low as demonstrated by the validated model above and supported by the anatomic distribution of nodal disease in the imputed cohort. Furthermore, the imputation of HPV status has been used in the past to improve statistical power . In the unlikely (<1 in 5) event of a false‐positive inclusion (i.e., inclusion of a patient who was truly HPV negative), this erroneously included patient's risk of recurrence or death would likely be higher than a true HPV‐positive patient, further reinforcing our conclusions that HPV‐induced CUP patients have an excellent prognosis, similar to HPV‐induced OPX cancer.…”
Section: Discussionsupporting
confidence: 59%
“…[410] Due to the improved survival in these cases, different staging for HPV-related oropharyngeal cancers has even been proposed,[11,12] and several HPV-OPSCC de-escalation trials are being conducted. [13,14] However, recurrence remains an issue for HPV-related OPSCC patients, and it is unclear which patients may benefit from de-escalated therapy or de-intensified follow-up. Many questions remain, including whether HPV-related biomarkers also have utility in identifying better survival among non-oropharyngeal HNSCC.…”
Section: Introductionmentioning
confidence: 99%
“…42, 43 Therefore, consensus is increasing that HPV status should be used as a stratification factor or be addressed in separate trials (HPV-related vs -unrelated disease) for which patients with oropharyngeal cancer are eligible. [44][45][46] Some clinicians have recently suggested that less-intense treatment may be adequate for HPV-positive oropharyngeal cancers (ie, deintensification) 47 ; however, the available data supporting this assertion are limited by retrospective analyses, variability in HPV testing method used, and short follow-up periods. 42,[47][48][49] Deintensification treatment protocols for HPV-associated, locally advanced oropharyngeal cancer are being investigated in ongoing clinical trials.…”
Section: Hpv and Treatment Of Oropharyngeal Cancermentioning
confidence: 99%